2021
DOI: 10.3390/v13081653
|View full text |Cite
|
Sign up to set email alerts
|

The Microvillar and Solitary Chemosensory Cells as the Novel Targets of Infection of SARS-CoV-2 in Syrian Golden Hamsters

Abstract: Patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of coronavirus disease 2019, suffer from respiratory and non-respiratory symptoms. Among these symptoms, the loss of smell has attracted considerable attention. The objectives of this study were to determine which cells are infected, what happens in the olfactory system after viral infection, and how these pathologic changes contribute to olfactory loss. For this purpose, Syrian golden hamsters were used. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Considering that in ammatory cell in ltration is not as abundant in the OM, it is presumed that the OE damage was induced by direct cell damage caused by the virus rather than by the effects of in ammatory cell in ltration. In the previously reported transnasal infection model of SARS-CoV-2, SARS-CoV-2 mainly infected the sustentacular cells, not the ORNs, and most of their cilia were lost early after infection 19,22 . It was also reported that SARS-CoV-2 could only be identi ed in the nasal septum of intranasal infected hamsters up to 3 days after infection 20 , which is consistent with our results.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Considering that in ammatory cell in ltration is not as abundant in the OM, it is presumed that the OE damage was induced by direct cell damage caused by the virus rather than by the effects of in ammatory cell in ltration. In the previously reported transnasal infection model of SARS-CoV-2, SARS-CoV-2 mainly infected the sustentacular cells, not the ORNs, and most of their cilia were lost early after infection 19,22 . It was also reported that SARS-CoV-2 could only be identi ed in the nasal septum of intranasal infected hamsters up to 3 days after infection 20 , which is consistent with our results.…”
Section: Discussionmentioning
confidence: 86%
“…Many studies have examined which OE cells are susceptible to infection by SARS-CoV-2, and it is now considered that the virus primarily infects the olfactory cilia and supporting cells but can also infect some basal ORN progenitors 9,19,21,22 . However, SARS-CoV-2 can also affect olfactory neurons, albeit slightly 21 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations